Penerapan Teori QIRĀ’AH MUBĀDALAH Terhadap Analisis Waktu dan Jumlah Jatuhnya dalam Konsep Talak Tiga Sekaligus - Hafidz, Maida (Tasamuh: Jurnal Studi Islam, 2022)
Divorce or Talak is the way of the end for couples (husband and wife), in order to avoid the mafsadat created by continuous contention without finding common ground or could be solved in a family way. Talak was given to the husband, but it was not to be used as a joke or taken by trivial. Therefore the pronounciation of thalaq three times in one time and considered to be deed to defend the concept of talak until now still be a debatable case and always being controversy. Thus the application of talak three should be fully formulated conceptually coresponding to the textual and contextual nas involving both of husband and wife as the subjects told by nas. This research is included in the form of data based on library research obtsined in the library scope by using descriptive analysis method. The result of this research is that the application of Qira’ah Mubadalah method here to find the corrcet answer to solve the problem of the multiple talak concepts, at least nas invites both sides man and women as the subjects of talking over the nas of talak law. In the field of fiqih, it implicitly that bot of they are equal. So that it is resiprocal that it’s stated in seeing the time is pronounced talak not only pay attention or consider the condition of the wife but also weighs and pay attention to the conditions and circumstances of the husband. Considering and weighing both of them (husband and wife) conditions in such a regimental way, it would have a greater impact on the fall of such a talak